Low threshold for nitrogen concentration saturation in headwaters increases regional and coastal delivery. (2nd April 2020) - Schmadel, Noah M; Harvey, Judson W; Alexander, Richard B; Boyer, Elizabeth W; Schwarz, Gregory E; Gomez-Velez, Jesus D; Scott, Durelle; Konrad, Christopher P
Abstract: River corridors store, convey, and process nutrients from terrestrial and upstream sources, regulating delivery from headwaters to estuaries. A consequence of chronic excess nitrogen loading, as supported by theory and field studies in specific watersheds, is saturation of the biogeochemically-mediated nitrogen removal processes that weakens the capacity of the river corridor to remove nitrogen. Regional nitrogen models typically assume that removal capacity exhibits first-order behavior, scaling positively and linearly with increasing concentration, which may bias the estimation of where and at what rate nitrogen is removed by river corridors. Here we estimate the nitrogen concentration saturation threshold and its effects on annual nitrogen export from the Northeastern United States, revealing an average 42% concentration-induced reduction in headwater removal capacity. The weakened capacity caused an average 10% increase in the predicted delivery of riverine nitrogen from urban and agricultural watersheds compared to estimates using first-order process assumptions. Our results suggest that nitrogen removal may fall below a first-order rate process as riverine concentration increases above a threshold of 0.5 mg N l −1 . Threshold behavior indicates that even modest mitigation of nitrogen concentration in river corridors above the threshold can cause a self-reinforcing boost to nitrogen removal.